Production of hhjj at the LHC - Dolan, Matthew J.; Englert, Christoph; Greiner, Nicolas; Spannowsky, Michael (Physical Review Letters, 2014)
Until now, a phenomenologically complete analysis of the hh+2j channel at the LHC has been missing. This is mostly due to the high complexity of the involved one-loop gluon fusion contribution and the fact that a reliable estimate thereof cannot be obtained through simplified calculations in the mt→∞ limit. In this Letter, we report on the LHC’s potential to access di-Higgs production in association with two jets in a fully showered hadron-level analysis. Our study includes the finite top and bottom mass dependencies for the gluon fusion contribution.
EPrint Processing Status: Full text deposited in DRO